2020
DOI: 10.3389/fphar.2019.01666
|View full text |Cite
|
Sign up to set email alerts
|

Edgeworthia gardneri (Wall.) Meisn. Water Extract Ameliorates Palmitate Induced Insulin Resistance by Regulating IRS1/GSK3β/FoxO1 Signaling Pathway in Human HepG2 Hepatocytes

Abstract: The flower of Edgeworthia gardneri (Wall.) Meisn is commonly used in beverage products in Tibet and has potential health benefits for diabetes. However, the mechanisms underlying anti-insulin resistance (IR) action of the flower of E. gardneri are not fully understood. This study aims to investigate the effects of the water extract of the flower of E. gardneri (WEE) on IR in palmitate (PA)-exposed HepG2 hepatocytes. WEE was characterized by UPLC analysis. PA-treated HepG2 cells were selected as the IR cell mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
(67 reference statements)
2
26
0
Order By: Relevance
“…Western blotting. Western blotting was performed as previously described (28). Briefly, serum exosomes or cells were lysed with RIPA protein extraction buffer (Beijing Solarbio Science & Technology Co., Ltd.) and incubated for 30 min at 4˚C.…”
Section: Inclusion and Exclusion Criteria Of The Patients And Healthy Volunteersmentioning
confidence: 99%
“…Western blotting. Western blotting was performed as previously described (28). Briefly, serum exosomes or cells were lysed with RIPA protein extraction buffer (Beijing Solarbio Science & Technology Co., Ltd.) and incubated for 30 min at 4˚C.…”
Section: Inclusion and Exclusion Criteria Of The Patients And Healthy Volunteersmentioning
confidence: 99%
“…Studies also found that E. gardneri improved insulin resistance in diabetic models. Our recent study showed that the water extract of the flower of E. gardneri (WEE) ameliorated palmitate-induced insulin resistance through regulating IRS1/GSK3β/FoxO1 signaling pathway in HepG2 hepatocytes ( Zhang Y. et al, 2020 ). Additionally, n-hexane extract of E. gardneri (EGH) improved insulin resistance in skeletal muscle via elevating GLUT4 expression both in vivo and in vitro ( Meng et al, 2019 ).…”
Section: Commonly Used Tibetan Materia Medica For Diabetes Mellitus Treatmentmentioning
confidence: 99%
“…The nuclear localization of p65, c-Jun, and IRF3 was detected with Nikon A1R Eclipse Ti confocal microscope (Nikon Corp., Tokyo, Japan) as previously described [21]. Brie y, cells were seeded into chamber slide for 12 h, and then treated with FSI (100 and 200 μg/mL) for 1h.…”
Section: Immuno Uorescence Stainingmentioning
confidence: 99%
“…The quanti ed cell lysates were assessed by Western blot analysis as described previously [21]. Brie y, cells (5×10 5 ) were seeded into 60-mm culture dishes, and then treated with FSI at various concentrations (200 and 400 μg/mL).…”
Section: Immunoblottingmentioning
confidence: 99%